KNOWLEDGE HIDING: THE FACTS AND CONCEPTS: A LITERATURE REVIEW - Habib Salem Affes; Faris Ahmed Abed (Scholars Digest Publishing, 2023)
Among the goals that sustainable development seeks to achieve is the availability of information and the right of the public to learn and benefit from experiences and make them available to all. The Research Knowledge Hiding has increased exponentially and rapidly over the past years, but results have not been collected or systematically examined with great care. Despite the acceptance, clarity and validity of this concept, there are limitations to the growth of this type of studies, especially with the intellectual difference from the point of view of superiors and subordinates. Superiors see it as a negative condition, while subordinates see it as a positive characteristic that underpins their position and role. In addition, the answer to the question must be found. Why do employees hide their knowledge? How can organizations encourage knowledge sharing? As a result, this current study aimed to integrate the different Knowledge Hiding literature through a systematic review of the literature to understand the growth of the Knowledge Hiding concept. The results of previous research were collected and discussed, as well as areas that require future research were revealed, and accordingly, (41) studies were systematically searched between dissertations and published research, and their ideas were evaluated, presented critically, and synthesized in a scientific context, which makes the concept easier and more understandable for scholars and practitioners. The current research not only answers some basic and not obvious questions about the concept, but also provides a composite approach from the diverse findings of the current literature that would help in drawing conclusions and making future decisions related to knowledge-hiding behaviors. In addition, the current research also highlights neglected areas. comparatively, which requires more research and empirical attention to advance the concept. As a result, the current research concluded that the concept needs more future studies, especially with regard to comparative studies related to the behavior of hiding knowledge and from different perspectives such as the social, cultural, economic and industrial sectors. The study is expected to motivate academics and researchers to advance the field in theory by providing a constructive platform for future studies in practice and the development of literature in the field.
Keywords: knowledge hiding, knowledge sharing.